2014
DOI: 10.3892/mmr.2014.2958
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-induced histone acetylation inhibition improves stress-induced gastric ulcer disease in rats

Abstract: Curcumin is known to possess anti‑inflammatory properties. Despite the fact that curcumin is known to be a strong inhibitor of H+, K+‑ATPase activity, the mechanism underlying the curcumin‑induced inhibition of the transcription of the H+, K+‑ATPase α subunit in gastric mucosal parietal cells remains unclear. The present study investigated the possible mechanism by which curcumin inhibits stomach H+, K+‑ATPase activity during the acute phase of gastric ulcer disease. A rat model of stress‑induced gastric ulcer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Curcumin H+, K + -ATPase Help in the treatment of gastric ulcers [27] IL-6,TNF-_, COX2 Reduces inflammation [28] SOCS1-3,p38MAPK Trans locates nuclear material in a different way.…”
Section: Gene Diseases Referencementioning
confidence: 99%
“…Curcumin H+, K + -ATPase Help in the treatment of gastric ulcers [27] IL-6,TNF-_, COX2 Reduces inflammation [28] SOCS1-3,p38MAPK Trans locates nuclear material in a different way.…”
Section: Gene Diseases Referencementioning
confidence: 99%
“…Recent evidence indicates that curcumin can be effective as a protective substance against the formation of stress-induced gastric lesions in rats [52], in part due to the inhibition of gastric secretory activity mediated by a strong inhibitory action on H + /K + ATPase activity in parietal cells of the rat stomach. Using a chromatin immunoprecipitation assay, He et al have demonstrated that curcumin inhibited the H + /K + ATPase promoter via histone acetylation, the gene and protein expression of the gastric H + /K-ATPase α subunit, thus resulting in the rise in pH and the amelioration of stress-induced gastric ulcerogenesis [52].…”
Section: Role Of Curcumin In the Protection Against Gastric Mucosamentioning
confidence: 99%
“…Recent evidence indicates that curcumin can be effective as a protective substance against the formation of stress-induced gastric lesions in rats [52], in part due to the inhibition of gastric secretory activity mediated by a strong inhibitory action on H + /K + ATPase activity in parietal cells of the rat stomach. Using a chromatin immunoprecipitation assay, He et al have demonstrated that curcumin inhibited the H + /K + ATPase promoter via histone acetylation, the gene and protein expression of the gastric H + /K-ATPase α subunit, thus resulting in the rise in pH and the amelioration of stress-induced gastric ulcerogenesis [52]. In another study, the anti-ulcer activity of curcumin in rats exposed to either chronic stress and/or unpredictable stressors was observed simultaneously with an evident improvement in memory deficit assessed in their study by the elevated plus maze test and by the overall improvement of homeostatic functions [53].…”
Section: Role Of Curcumin In the Protection Against Gastric Mucosamentioning
confidence: 99%
“…In rat animal model, curcumin was shown to have a preventive and therapeutic effect in gastric ulcer disease by acting as a strong inhibitor of H+, K+-ATPase activity. It downregulated the acetylation of histone H3, thereby inhibiting the transcription and expression of H+, K+-ATPase gene [ 87 ]. Curcumin strongly inhibits the expression of LPS-induced inflammatory mediators along with IL-6, TNF-α and COX-2 mRNAs in macrophages via modulating the expression of cytokine signaling-1(SOCS-1 and 3) and p38 MAPKsuppressors.…”
Section: Nutrient-gene Interaction In Life-style Associate Diseasesmentioning
confidence: 99%